Prevalensi obesitas dan hubungan konsumsi fast food dengan kejadian obesitas pada remaja SLTP kota dan desa di Daerah Istimewa Yogyakarta - Mahdiah Mahdiah; Hamam Hadi; Susetyowati Susetyowati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2004)
Background: The improvement in socioeconomic status has led to sedentary life style and more fast food consumption. Whether fast food consumption contributes to obesity in Indonesian adolescents remains unclear.Objective: The study was conducted to estimate the prevalence of obesity and to assess the association between fast food consumption and obesity in junior high school students.Methods: A cross-sectional survey was conducted in 2003 to estimate the prevalence of obesity in adolescent students of Yogyakarta Special Province. Subjects of this survey were junior high school students from urban (n= 4747) and rural areas (n=4602) were included in this survey. To further analyze the association between food consumption and obesity, a sample of 140 obese (of 460 obese students) and 140 non obese students (of 8889 non obese students) was randomly selected. Data on fast food consumption were collected using Food Frequency Questionnaire (FFQ) method from the selected obese and non-obese sample.Results: The prevalence of obesity among adolescent students was 7.9% in urban and 2% in rural areas. There was a significant difference in variety, quantity, and frequency of fast food consumption per month and hereby energy intake from fast food between obese and non-obese adolescent students (p<0.05).Conclusions: The prevalence of obesity in urban area was much higher than that in rural area. Obese students consumed fast food more frequently and more variably than non-obese students.